DISCOURSE ANALYSIS OF KAJAOLALIDDONG PAPPASENG IN THE FORMATION OF STUDENT CHARACTERS IN A MODEL SCHOOL IN THE DISTRICT OF BONE - Akkase Teng, Muhammad Bahar; Rijal, Syamsu; Badollahi, Muh. Zainuddin (PEOPLE: International Journal of Social Sciences, 2019)
Since 2016, the South Sulawesi Education Assurance Agency has tried to organize and improve the quality of education throughout the province through establishment of a model school in each of its districts / cities. The educational program applied in the model schools is to strengthen the local characters of Bugis-Makassar, Toraja and Luwu or Massenrengpulu through harmonization of thought and behavior of students with support of the government, schools, families and communities as stakeholders of the National Mental Revolution Movement (NMRM). In fact, this educational program is intended to improve the students’ morality through harmonization of heart, feeling, thought and body through sufficient understanding of the local values implied in Kajaolalido Pappaseng (the testament of Kajaolalido, the legendary Bugis scholar). The study employed discourse analysis methods to strengthen the students’ local values in the model schools in Bone, one of the largest districts in the province. Some simulations of character implementation models were tested. Of the four simulation models applied (habituation, learning time, values strengthening and extracurricular), only two were employed to strengthen the character education through the use of discourse analysis methods; habituation and extra-curricular activities. The findings reveal that the model school students are very enthusiastic about recognizing and exploring the values ​​of local wisdom through the discourse analysis methods, and more importantly, the use of those methods leads both the teachers and students to discover at least five character values; honesty, work ethic, mutual cooperation, determination and courage.